2023
DOI: 10.1111/echo.15650
|View full text |Cite
|
Sign up to set email alerts
|

Early impairment of right ventricular systolic function in patients with prediabetes and type 2 diabetes mellitus: An analysis of two‐dimensional speckle tracking echocardiography

Abstract: BackgroundType 2 diabetes mellitus is a metabolic disease that affects multiple target organs. Current data on right ventricular damage in type 2 diabetes, especially in prediabetes, are limited. Due to the anatomical characteristics of the right ventricle, the assessment of the right ventricle by conventional echocardiography is difficult, whereas the ultrasound two‐dimensional speckle tracking echocardiography can provide information on myocardial systolic function by tracking the motion information of myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…According to our study, 27.97% of prediabetes patients developed T2DM. The progression to T2DM was highest in patients with coexistent IFG and IGT, which is consistent with the findings of Wu et al [ 13 ]. We found that most patients with prediabetes had IFG or IGT, and coexistent IFG and IGT accounted for 20%.…”
Section: Discussionsupporting
confidence: 92%
“…According to our study, 27.97% of prediabetes patients developed T2DM. The progression to T2DM was highest in patients with coexistent IFG and IGT, which is consistent with the findings of Wu et al [ 13 ]. We found that most patients with prediabetes had IFG or IGT, and coexistent IFG and IGT accounted for 20%.…”
Section: Discussionsupporting
confidence: 92%